The Evolution of Lymphangioleiomyomatosis (LAM) Management: From Hormonal Manipulation to Targeted Inhibition of the mammalian target of rapamycin (mTOR) Pathway (Research, Society and Development, 2025)
Lymphangioleiomyomatosis (LAM), a rare and progressive lung disease predominantly affecting women, has undergone a significant transformation in its therapeutic management over recent decades. This review aims to critically analyze this evolution, contrasting historical hormonal manipulation strategies with modern therapy targeted at inhibiting the mammalian target of rapamycin (mTOR) pathway, elucidating the transition to the current treatment standard. Conducted as a narrative review of scientific literature, the analysis demonstrates that hormonal approaches, despite an initial biological rationale involving receptors and estrogenic interactions, did not show robust efficacy in modifying the progression of lung disease. The turning point occurred with the identification of the mTOR pathway as central to LAM pathogenesis, driven by TSC gene mutations. This discovery led to the development and clinical validation of mTOR inhibitors, such as sirolimus and everolimus, which have been shown to stabilize lung function and improve patient outcomes. Currently, mTOR inhibitors constitute the therapeutic gold standard, representing a milestone in precision medicine for LAM treatment. While consolidating the evidence supporting this paradigm shift, this review also highlights persistent challenges and directions for future research, including treatment optimization, the identification of new biomarkers, and the search for complementary therapies.